The girl who saved Christmas - Haig, Matt, 1975- (Alfred A. Knopf, 2017)
Amelia Wishart's Christmas spirit helped Santa get the extra boost of magic he needed to make his first trip around the world. When she's sent to the workhouse, now-orphaned Amelia's hope begins to drain away. Santa sets out to find her with the help of his reindeer, a curious cat, and Charles Dickens.